Adjustment and Growth in Latin America - Conable, Barber B. (World Bank, Washington, DC, 2017)
Barber B. Conable, President of the World Bank, discussed how in Mexico, the decade of the Eighties began with a massive increase in the size of government, its ownership and interventions, and with an unmanageable debt. By the decade's end, Mexico had launched one of the most ambitious, courageous and determined programs of economic reform and institutional change recently undertaken in any country, developed or developing. For those whose incomes were eroded and for those who lost their jobs, these last seven years have been an eternity. But the Government of Mexico is keen to broaden human opportunity and create an efficient and mobile economic structure. The stage is set in Mexico for a resumption of growth and the resultant alleviation of hardship. The Government is aware that the benefits of this development should be distributed widely through emphasis on education and human services. The World Bank shares these goals and expect to contribute to their achievement with analysis, advice, our own funds, and help in mobilizing other sources of finance.